Multimedia Interaktif: Media Belajar untuk Membuat Paspor RI melalui Simulasi - Sembiring, Evaliata Br; Nurrahmah, Nurrahmah (JOURNAL OF DIGITAL EDUCATION, COMMUNICATION, AND ARTS (DECA), 2019)
APM is an Innovation in 2017 implemented at the Immigration class II Tanjung Balai Karimun Office in making an Indonesian passport. People complain about the new system. Generally, there is a lot of files that need to be prepared and confused to run the procedure. the development of technology can answer these complaints through various media. One of the media that can be used is Interactive Multimedia. Through this media, people can be guided in preparing files and carrying procedures under the activities carried out at the immigration office. therefore, the model is applied in the form of simulation.This research applies the ADDIE model so that the implementation started with a needs analysis, system design based on needs, media development, implementation and evaluation of the applied media. the results of the study are: (1)The results of the needs analysis regarding information on submitting an application for an Indonesian passport there are 69.87% of applicants not yet aware of the passport application procedures through the APM application; (2)Interactive multimedia about the Indonesian passport application simulation using the APM application produced as one of the information media for the community by applying the ADDIE model packaged in format (SWF) and (exe), applying the navigation button feature for user interactivity, content format in the form of text, images, and 2D animation video’s; (3)Formative and summative evaluation results enable interactive multimedia as a learning medium to assist the community in completing files and applying for an Indonesian passport in accordance with actual implementation at the immigration office.